Superficial CD34 Positive Fibroblastic Tumour, A Mesenchymal Tumour with Borderline Malignant Potential: A New Entity - Walia, Gurpreet Kaur; Kinra, Prateek; Malik, Ajay (Annals of Pathology and Laboratory Medicine, 2021)
Superficial CD34 positive fibroblastic tumour (SCD34FT) is a distinct mesenchymal tumour of superficial soft tissues which has an intermediate malignant potential and is a recently introduced entity in the WHO classification. We present a case report of a 32-year-old male patient with SCD34FT. The tumour was located on right forearm and was essentially superficial in location. Wide local excision of the tumour was done. On histopathological examination, the tumour was composed of highly pleomorphic spindled as well as epithelioid cells with granular eosinophilic cytoplasm and numerous bizarre lobulated nuclear forms with few showing intranuclear inclusions. However, the mitotic count was very low. On immunohistochemistry (IHC), tumour cells were diffusely positive for vimentin and CD34 (characteristic of SCD34FT). During clinical follow-up, the patient is asymptomatic since the time of his surgery one year back. SCD34FT is a mesenchymal tumour of borderline malignant potential which is restricted to the superficial location.